Adaptive Feed Plant Association Model For Improved Post-mining Land In Karangasem Regency - W. Suarna; N.N. Candraasih K; M.A.P. Duarsa (Environmental Research Center (PPLH) of Udayana University, 2014)
A study has been carried out to obtain the model legume association with superior grassplants that are adaptive to repair post-mining land on dry land. In the early stages, theresearch carried out on non-mining land to observe potential association models thatpredicted very suitable to recover the post-mining land. Experiment using a randomizedblock design with 12 combinations between grasses, legumes, and mycorrhizal and repeatedthree times. Grass used is Panicum maximum cvTrichoglumeand BrachiariaBrizanta, whilelegumes are used Centrocemapubescens and Clitoriaternatea. The results showed thatbased on analysis of growth and forage yield variables, almost all association models canbe developed in dry land, and models the association between panikum, Brachiaria andcentrocema can provide the highest results as much as 11.42 tons per ha of forage fresh or1,37 tons of dry forage per ha .